Antioxidant and immunomodulatory activities of sulphated polysaccharides from purple glutinous rice bran (Oryza sativa L.) - Siriluck Surin (2018)
© 2017 Institute of Food Science and Technology This research aimed to extract polysaccharides and improve the property of sulphate-modified purple glutinous rice bran, cv. Kum Doi Saket. The effects of temperature, ratio of sulphur trioxide–trimethylamine (STMA) to sample and reaction times were studied. The results showed that the degree of substitution (DS) of sulphated polysaccharides was 0.01–0.53. Low molecular weight sulphated polysaccharides were obtained, and the functional groups of the sulphated polysaccharides were confirmed using FT-IR. No enhancement of the antioxidant activity of the sulphated polysaccharides was observed. Interestingly, immunomodulatory activity, including inducing cytokine production (iNOS, TNF-α, IL-1β and IL-10) via up-regulated mRNA expression, was significantly increased by 10–86% when compared to the crude polysaccharides.